GRANITOIDS, RARE-METAL PEGMATITES AND ТА-NB MINERALIZATION OF SHPOLIANO-TASHLYK ORE AREA (INGUL MEGABLOCK, UKRAINIAN SHIELD) - Hrinchenko, О.; Bondarenko, S.; Mironchuk, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Composition of granites, genetically associated pegmatites and superimposed metasomatites distributed within Shpoliano-Tashlyk ore area (Ingul megablock) is considered. It is established, that on the basis of similarity in their petrographic and petrochemical features granitoids of the area can be related to single complex. Features of ore mineralization are defined by both composition of granitoids (Sgranites) after which rare-metal pegmatites are formed and intensity of superimposed metasomatic alterations. Main minerals-concentrators of Тa and Nb mineralization in granitic pegmatites and metasomatites are represented by minerals of three isomorphic series – columbite-tantalite (Fe,Mn)(Nb,Ta,Ti)2O6, ilmenorutile-struverite (Ti,Nb,Ta)O2 and pyrochlore-microlite (Ca,Na)2Ta2O6(O,B,OН,F). Depending on geological setting such ore minerals as tapiolite, ixiolite, cassiterite, uraninite, nigerite, gahnite are commonly found in association with these minerals. Сhemical composion of tantalo-niobates sampled from ore-bearing pegmatites and metasomatites is investigated by microprobe analysis. Most minerals of columbite-tantalite series are characterized by distinct and rhythmic internal zonality and contrasting mosaic structure which are related to considerable heterogeneities of their chemical composition. Within one aggregate mineral phases with wide range of values – from 9,80 to 71,0 % for Ta2O5 and from 10,6 to 70,1 % for Nb2O5 – are established. Among minerals ferruginous varieties which composition relates to Fe-columbite-tantalites (Nb2O5/Ta2O5 = 1–1,2; FeО/MnО = 2,5–6) prevail. Columbite-tantalites are characterised by high contents of admixture elements present (%): TiО2 – to 5,88; WО3 – to 3,70; SnО2 – to 9,20; Sc2O3 – to 5,40. Scandium ores occur as scandium-rich minerals that are mostly confined to the minerals of columbite-tantalite series found in Polohivka ore field. On the Ukrainian Shield high contents of Sc2O3 in tantalo-niobates are established for the first time. Minerals of ilmenorutile-struverite series do not quantitatively yield to minerals of columbite-tantalite series. For minerals of this series Nb2O5/Ta2О5 ratio varies in the range of 0,6-1,4. Among characteristic admixture-elements are prevailed (%): SnО2 – to 3,1, V2O5 – to 5,05; FeО – to 11,51, Cr2O3 – to 1,20. Minerals of pyrochlore-microlite series are of subordinate importance. For the first time by results of U-Pb dating of columbite-tantalites from Mostove ore manifestation (Shpoliano-Tashlyk area) the age of Тa-Nb mineralization is established to be about 1965 ± 25 million years.
Keywords: Rare-metal pegmatites; Та-Nb mineralization; Ukrainian Shield